Pengaruh Pupuk Kalsium dan Kalium terhadap Pertumbuhan dan Kualitas Hasil Sawi Hijau (Brassica rapa L.) - Monica Intan Aryandhita; Dody Kastono (Universitas Gadjah Mada, 2021)
Mustard (Brassica rapa L.) is one of vegetable that cultivated and consumed by people in Indonesia regions. Using calcium fertilizer in mustard cultivation is less important, so that it is done when symptoms of calcium deficiency affect the quality of crop yield such as tip burn. Calcium fertilization could overcome calcium deficiency, but plant will undergo potassium deficiency as side effect. Foliar application of calsium fertilizer was used to avoid negative interaction between calcium and phosphate in the soil so that good quality yield and growth could be produced. A research was conducted on August-October 2019 at Kebun Percobaan Tri Dharma, Agriculture Faculty, Gadjah Mada University, Banguntapan, Bantul, Yogyakarta. The research used RCBD with two factors which were the concentration of calcium fertilizer (0, 2, 4, and 6 g/l) and the second factor was the dosage of KCl fertilizer (0, 100, 200, and 300 kg/ha). Concentration showed amount of calcium fertilizer mixed in a liter of water and dosage showed amount of fertilizer applied per plant. Result of the research showed that interaction between calcium concentration and phosphate dosage did not increase mustard growth and yield but had potensial in increasing texture and taste of mustard by applying 4 and 6 g/l calcium concentration with 100 kg/ha phosphate dosage, while 2 and 4 g/l calcium concentration with 200 kg/ha dosage could increasing sweet taste in mustard. Calcium fertilizer concentration increased mustard consumption index. The more amount of phosphate fertilizer dosage applied (> 300 kg/ha) could decrease mustard fresh weight